Guide to economics for Filipinos - Villegas, Bernardo M. (Manila, 2010)
This edition of his popular introductory textbook in economics, Dr. Bernardo villegas illustratos how a thorough understandine of the strengths and weaknesses of the market economy requires a strong foundation on what is known as microeconomics before getting into macro-economics. This student-friendly text offers a multidisciplinary approach to economics to enable the student to understand economic problems in the context of the overall approach to total human development.
Keywords: Economics